2011
DOI: 10.1007/s11060-011-0705-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD105 (endoglin)-positive stem-like cells in rhabdoid meningioma

Abstract: To investigate the tumor-initiating cells (TICs) in rhabdoid meningioma (RM), a population of CD105-positive cells isolated from a fresh RM surgical sample was analyzed for proliferative activity, self-renewal ability, tumorigenic ability, multilineage differentiation potential, as well as chromosomal aberrations. The results showed that isolated CD105-positive cells could be maintained for more than 50 generations in vitro. These cells exhibited increased proliferative activity and single-cell tumor sphere-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Endoglin-positive meningioma cells have similar increased tumorigenicity and capacity to differentiate into adipocytes and osteocytes. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Endoglin-positive meningioma cells have similar increased tumorigenicity and capacity to differentiate into adipocytes and osteocytes. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated the isolation and characterization of meningioma stem-like cells (21,23). The relationship between these so-called meningioma CSCs (mCSCs) and the MS-MSLCs isolated from meningiomas and described in the present study is not clear.…”
Section: Pathologymentioning
confidence: 69%
“…Although meningioma is one among the most common brain tumors also in Korea (20), little is known about meningioma cell biology. The recent successful isolation and characterization of CSCs from meningioma has provided a better understanding of meningioma biology (21)(22)(23). Components of the meningioma stroma are also likely important, as supported by previous studies (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, we presume that meningioma tumor stem cells may be responsible for these events. According to recent reports, CSC-like cells may be present in meningiomas (13,17,30). Traditionally, Nestin, CD133 and Sox2 are regarded as CSC markers, but they could also be considered specific markers for BTSCs (28).…”
Section: █ Discussionmentioning
confidence: 99%